Faculty and administrators eating at table - Unknown (Tufts Archival Research Center, 2007)
8x10. This date is approximate. Identified on the back: leftside- #2- Prof. R. J. Bartlett, #3- Savelle Davis, #4- Prof. Leo Gross, #5- Dr. Gregory Wolfe, #6- Prof. William Kelly; rightside- #1- VP Theodore Tredinnick, #2- Antony Cordozo, #3- Prof. Albert Imlah, #5- David Larson, #6- Prof. Norman Padelford